2018
DOI: 10.1371/journal.pone.0205952
|View full text |Cite
|
Sign up to set email alerts
|

Reported methods for handling missing change standard deviations in meta-analyses of exercise therapy interventions in patients with heart failure: A systematic review

Abstract: BackgroundWell-constructed systematic reviews and meta-analyses are key tools in evidenced-based healthcare. However, a common problem with performing a meta-analysis is missing data, such as standard deviations (SD). An increasing number of methods are utilised to calculate or impute missing SDs, allowing these studies to be included in analyses. The aim of this review was to investigate the methods reported and utilised for handling missing change SDs in meta-analyses, using the topic of exercise therapy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…For the primary outcome, we obtained mean changes of stress scores and standard deviation from baseline for both arms, with conversion from pre-and post-intervention stress scores if not otherwise available using a correlation coefficient of zero. 38,39 When multiple scales are present in a study, preference was given to measures more specific for stress and those that are more commonly used in other identified studies. In decreasing order of preference, these are the Perceived Stress Scale (PSS), the Maslach Burnout Inventory for emotional exhaustion (MBI-EE), the Nursing Stress Scale (NSS), and others if these are not available.…”
Section: Data Extractionmentioning
confidence: 99%
“…For the primary outcome, we obtained mean changes of stress scores and standard deviation from baseline for both arms, with conversion from pre-and post-intervention stress scores if not otherwise available using a correlation coefficient of zero. 38,39 When multiple scales are present in a study, preference was given to measures more specific for stress and those that are more commonly used in other identified studies. In decreasing order of preference, these are the Perceived Stress Scale (PSS), the Maslach Burnout Inventory for emotional exhaustion (MBI-EE), the Nursing Stress Scale (NSS), and others if these are not available.…”
Section: Data Extractionmentioning
confidence: 99%
“…Regarding sample size, the aim was to achieve a precision estimate of at least 0.6 points in terms of the halfwidth of the 95% confidence interval (CI). As the effect size was unknown and no previous studies with the products were available, the mean of the baseline standard deviations was used [ 26 ] from a study of a different ointment (containing sucralfate) with similar indications [ 20 ]. Thus, under the assumption that the standard deviation of the change in mSSS is 1.5 points, and the precision estimate in terms of the 95% CI is ± 0.6 points, a minimum of 24 patients had to be included in the analysis for both products.…”
Section: Methodsmentioning
confidence: 99%
“…Sixty-eight percent of the researchers surveyed by Weir, et al [3] had encountered studies with unreported sample statistics when conducting systematic reviews. Batson and Burton [4] discovered that 41 percent of meta-analyses of diabetes studies reported specific efforts, such as imputation, to address the problem of missing variances, and Pearson and Smart [5] obtained similar findings among meta-analyses of studies that examined the effect of exercise in heart failure patients. Sangnawakij, et al [6] found 38 studies of surgical procedures that reported neither variances nor standard deviations, and Wiebe, et al [7] examined more than 100 systematic reviews that were plagued by missing variance data.…”
Section: Introductionmentioning
confidence: 91%
“…Such work is often seriously impeded, however, when the primary studies fail to report basic statistical information from their samples, such as means or standard deviations. This problem of unreported sample statistics in published clinical trials and other basic research is well-documented ( [1][2][3][4][5][6][7]). For example, 87 percent of the randomized, controlled trials of antidepressants reviewed by Streiner and Joffe [1] failed to fully report the mean, standard deviation, and/or sample size; similarly, more than 80 percent of the clinical trials reviewed by Chan, et al [2] reported insufficient statistical information for inclusion in meta-analysis.…”
Section: Introductionmentioning
confidence: 99%